Traumatic intrusion of primary tooth: a case Report - Zabokova-Bilbilova Efka; Stefanovska Emilija (Medicinski fakultet i Klinika za stomatologiju, Niš, 2021)
Introduction: Anterior teeth are of utmost importance with regard to chewing, speaking, and beauty. Therefore, any traumatic dental injury has psychologically undesirable effects on children and their parents. The present study reported a case of a traumatic dental injury induced by falling off a chair and referral to an emergency department as well as measures taken for dental reconstruction and patient's improvement. Case Report: Parents with a 3-year-old girl came to the Clinic for Pediatric and Preventive Dentistry at University Dental Clinic Center "St. Panteleimon", Skopje with injuries to her face and oral structures resulting from a fall from a chair. The extraoral examination revealed a laceration on the submental skin surface and an injury to the upper lip. The child was examined and it was found that the maxillary left primary central incisor was compressed in the alveoli. The surrounding soft tissue was injured. Intraorally, the anterior segment of the maxilla showed injury consistent with low-velocity blunt-force trauma, including several lacerations of the gingival tissues. The patient's maxillary left central incisor was intruded from the socket. Conclusion: The prognosis of many cases of dental injuries is time-dependent. The intrusion of a tooth can have ramifications and the possibility that it has been fully intruded should be considered. The use of a radiograph is of great importance for the correct diagnosis of deciduous tooth intrusion.